Biological Treatments for Tendon and Ligament Abnormalities: A Critical Analysis Review. Issue 6 (21st June 2016) - Fralinger, David J.; Kaplan, Daniel J.; Weinberg, Maxwell E.; Strauss, Eric J.; Jazrawi, Laith M.
Abstract : The poor intrinsic healing potential of tendon and ligamentous tissue has driven the search for biological agents that can improve healing, most notably platelet-rich plasma (PRP) and autologous stem cells. Current evidence best supports the use of PRP as treatment for chronic, degenerative tendinopathies such as lateral epicondylitis of the elbow or patellar tendinopathy. It does not support the use of PRP to promote tendon or ligament-to-bone healing in rotator cuff repair or anterior cruciate ligament (ACL) reconstruction. Clinical evidence regarding the use of autologous stem cells as treatment for tendon and ligament abnormalities is currently limited. However, the initial results appear to be promising, particularly following rotator cuff repair. A major limitation in the evaluation of current data is the lack of standardization in the preparation and composition of PRP, which are often not reported. Future investigators should make an effort to report the method of preparation and final composition of PRP used. Autologous stem cells were most often harvested from bone marrow aspirate but were occasionally derived from dermal tenocyte cells. Recent studies have explored new sources for stem cells, including adipose tissue, peripheral blood, and human amniotic tissue. We expect that clinical data evaluating these treatments will soon emerge.